Fourth IFIP International Conference on Theoretical Computer Science- TCS 2006
DOI: 10.1007/978-0-387-34735-6_21
|View full text |Cite
|
Sign up to set email alerts
|

Reusing Optimal TSP Solutions for Locally Modified Input Instances

Abstract: Abstract. Given an instance of an optimization problem together with an optimal solution, we consider the scenario in which this instance is modified locally. In graph problems, e. g., a singular edge might be removed or added, or an edge weight might be varied, etc. For a problem U and such a local modification operation, let lm-U (local-modification-U ) denote the resulting problem. The question is whether it is possible to exploit the additional knowledge of an optimal solution to the original instance or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
1
37
1
Order By: Relevance
“…Since then, reoptimization has been applied to various problems like the TSP [4][5][6][7], the Steiner tree problem [8][9][10][11], the shortest common superstring problem [12,13], the knapsack problem [14], and several covering problems [15].…”
Section: Overview Of Reoptimization Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, reoptimization has been applied to various problems like the TSP [4][5][6][7], the Steiner tree problem [8][9][10][11], the shortest common superstring problem [12,13], the knapsack problem [14], and several covering problems [15].…”
Section: Overview Of Reoptimization Resultsmentioning
confidence: 99%
“…We denote the resulting reoptimization problem by Inc-Edge-Reopt-∆TSP. This reoptimization problem is N Phard [6,19], but it admits an approximation algorithm which improves over the one from Christofides. The proof of this theorem is based on the following idea which can be used for several other reoptimization problems as well.…”
Section: Overview Of Reoptimization Resultsmentioning
confidence: 99%
“…This concept of reoptimization was mentioned for the first time in [20] in the context of postoptimality analysis for a scheduling problem. Since then, the concept of reoptimization has been investigated for several different problems like the traveling salesman problem [1,3,8,12], knapsack problems [2], covering problems [7], and the shortest common superstring problem [6]. In these papers, it was shown that, for some problems, the reoptimization variant is exactly as hard as the original problem, whereas reoptimization can help a lot for improving the approximation ratio for other problems, for an overview of some results see also [11].…”
Section: Introductionmentioning
confidence: 99%
“…Postoptimality analysis deals with the related question of how much an instance may be altered without changing the set of optimal solutions, see, e.g., [19]. Since then, the concept of reoptimization has been successfully applied to various problems like the traveling salesman problem [1,3,7,8], the Steiner tree problem [4,10,11], the knapsack problem [2], and various covering problems [5]. A survey of reoptimization problems can be found in [9].…”
Section: Introductionmentioning
confidence: 99%